2021
DOI: 10.1016/j.pcd.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Indirect impact of the COVID-19 pandemic on hospitalisations for cardiometabolic conditions and their management: A systematic review

Abstract: Background The Coronavirus disease 2019 (COVID-19) pandemic has led to a dramatic crisis in health care systems worldwide. These may have significant implications for the management of cardiometabolic diseases. We conducted a systematic review of published evidence to assess the indirect impact of the COVID-19 pandemic on hospitalisations for cardiovascular diseases and their management. Methods Studies that evaluated volume of hospitalisations for cardiometabolic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…In addition, being afraid of infection could have limited patients´ attendance at medical appointments during the pandemic, which in turn may have delayed diagnoses or even not detecting them. The results of our study are in line with recent reviews showing a decrease in the number of hospitalizations due to ischemic heart disease during the COVID-19 pandemic ( Seidu et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, being afraid of infection could have limited patients´ attendance at medical appointments during the pandemic, which in turn may have delayed diagnoses or even not detecting them. The results of our study are in line with recent reviews showing a decrease in the number of hospitalizations due to ischemic heart disease during the COVID-19 pandemic ( Seidu et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have assessed and reported the extent to which consultation rates of patients and healthcare services have been impacted during the COVID-19 pandemic compared to pre-pandemic times. These have included patient delays in seeking medical care, declines in hospitalisations for acute medical conditions such as strokes and myocardial infarctions (with reductions ranging from 20.2 to 73.0%), impact on routine cancer care, less utilisation of in-hospital procedures such as coronary angiographies, postponing or cancellation of surgical procedures, and shorter length of hospital stays [ 9 , 10 , [18] , [19] , [20] ]. Several studies have also reported on the impact of the COVID-19 pandemic on primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…Consultation rates of patients for medical conditions, their management and outcomes have all been adversely impacted by the COVID-19 pandemic [ 8 ]. Compared to the pre-pandemic period, there has been a substantial decrease in admissions for acute medical conditions, longer delays between the onset of the symptoms and hospital treatment, less utilisation of inhospital procedures, and reduction in access to care for chronic diseases [ [9] , [10] , [11] ]. Even primary care services (the first point of contact in the healthcare system) have had to restructure their services to minimise the burden of COVID-19, whilst trying to deliver necessary care.…”
Section: Introductionmentioning
confidence: 99%
“…The most immediate indirect effects were likely seen in both purposeful and inadvertent redirection of health services (45)(46)(47). A population-based study of the primary care practices in England observed a 70% decrease in the rate of diabetes diagnoses and a 30% decrease in HbA 1c testing during April 2020; both of these rates gradually returned to usual levels over the subsequent 6 months (47).…”
Section: Health System and Service Effectsmentioning
confidence: 99%